2008
DOI: 10.1038/jhh.2008.140
|View full text |Cite
|
Sign up to set email alerts
|

Association between pregnancy-related hypertension and severity of hypertension

Abstract: Hypertension in pregnancy is an emerging sex-specific risk factor for cardiovascular disease and may lead to more severe hypertension after pregnancy. The objectives of this study were to investigate the frequency of pregnancy-related hypertension among patients referred to a hypertension clinic and its association with the severity of hypertension and evidence of end-organ damage. In this cross-sectional study, women with hypertension were submitted to a systematic clinical evaluation. The occurrence of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hypertension occurring during pregnancy may lead to preeclampsia, a serious condition associated with substantial maternal and fetal morbidity and mortality (Solomon and Seely 2006). Hypertension during pregnancy may also predispose women to development or increased severity of future cardiovascular disease (Garovic and Hayman 2007; Moreira et al 2009). …”
mentioning
confidence: 99%
“…Hypertension occurring during pregnancy may lead to preeclampsia, a serious condition associated with substantial maternal and fetal morbidity and mortality (Solomon and Seely 2006). Hypertension during pregnancy may also predispose women to development or increased severity of future cardiovascular disease (Garovic and Hayman 2007; Moreira et al 2009). …”
mentioning
confidence: 99%
“…Through linear regression and funnel plots, we found that studies on HDP ( P = 0.4639) and PE ( P = 0.5380) had no publication bias ( Figure 4 ). Figure 5A shows that when omitting one of these studies ( 22 ), the sensitivity analysis of the HDP group showed an OR of 4.10 (95% CI 2.49–6.74), which was nearly the same outcome as the total pooled effect (OR 3.61, 95% CI 2.18–6.00). Similarly, when omitting other studies, women with HDP were at higher risk for developing chronic hypertension than healthy controls.…”
Section: Resultsmentioning
confidence: 97%